The Development Government Agencies Sarmi (A Study on the Regional Employment Board Sarmi) - Aweno, Elisabeth; Dengo, Salmin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Potential Development of Human Resources is very important in order, improve the quality ofpersonnel who are competent and capable of carrying out duties as civil servants and even the community.Human resource development can be done by means of education and training of both the education andin-service training as well as education and training positions as stipulated in Government Regulation No.101 of 2000 on Education and Training. To determine the potential development of human resourcespersonnel in Sarmi, in this study was conducted using qualitative informant number as many as 10 people.Efforts Potential Development of Human Resource Apparatus in Sarmi is done by means of education andin-service training and occupation is already running but is not optimal, it is because first, the RegionalEmployment Board Sarmi as implementing education and training is still less put through an evaluation ofthe results of education and training ; Secondly, there is still a shortage of teachers (widyaswara) so this isone of the obstacles in the implementation of education and training in Sarmi.To realize the potential of human resources personnel in Sarmi, the strategic steps that must be done isnecessary to evaluate the implementation of education and training, and should be pursued additionalteaching staff (widyaswara) in order to expedite the implementation of education and training nets. Besides,it is expected by the education and training are implemented can have a large impact on the performanceof government officials SarmiKeywords: Potential of Human Resource Development Government Personnel